Relation between nutrition and health in dairy herds (2009)
Incidence of health and production problems related to feeding, nutrition and/or metabolism have being growing in dairy herds. Early diagnosis allows their reduction and consequently reduces economic losses. Monitoring nutritional status periodically allows to identify possible causes of nutritional unbalances and/or mistakes in feeding practices and establish corrective measurements.